Wheat landrace genome diversity - Wingen, Luzie U.; West, Claire; Leverington-Waite, Michelle; Collier, Sarah; Orford, Simon; Goram, Richard; Yang, Cai-yun; King, Julie; Allen, Alexandra M.; Burridge, Amanda; Edwards, Keith J.; Griffiths, Simon (Genetics Society of America, 2017)
Understanding the genomic complexity of bread wheat (Triticum aestivum L.) is a cornerstone in the quest to unravel the processes of domestication and the following adaptation of domesticated wheat to a wide variety of environments across the globe. Additionally, it is of importance for future improvement of the crop, particularly in the light of climate change. Focussing on the adaptation after domestication, a nested association mapping (NAM) panel of 60 segregating bi-parental populations were developed mainly involving landrace accessions from the core set of the Watkins hexaploid wheat collection optimized for genetic diversity (WINGEN et al. 2014). A modern spring elite variety, ’Paragon’, was used as common reference parent. Genetic maps were constructed following identical rules to make them comparable. In total, 1,611 linkage groups were identified, based on recombination from an estimated 126,300 crossover events over the whole NAM panel. A consensus map, named landrace consensus map (LRC) was constructed and contained 2,498 genetic loci. These newly developed genetics tools were used to investigate the rules underlying genome fluidity or rigidity, e.g. by comparing at marker distances and marker orders. In general, marker order was highly correlated, which provides support for strong synteny between bread wheat accessions. However, many exceptional cases of incongruent linkage groups and increased marker distances were also found. Segregation distortion was detected for many markers, sometimes as hot-spots present in different populations. Furthermore, evidence for translocations in at least 36 of the maps was found. These translocations fell, in general, into many different translocation classes, but a few translocation classes were found in several accessions, the most frequent one being the well known T5B:7B translocation. Loci involved in recombination rate, which is an interesting trait for plant breeding, were identified by QTL analyses using the crossover counts as a trait. In total, 114 significant QTL were detected, nearly half of them with increasing effect from the non-reference parents.